Simulação numérica de camadas de mistura em desenvolvimento temporal e espacial, usando a Técnica Espectral da Colocação - Santos, Marcelo Fernandes dos (1998)
The objective of the present work was computacional code developing, applying the Collocation Spectral Technique to simulate the compressible and turbulent mixing layers. in temporal and spatial developments, described by the complete conservative governing equations. It was implemented an explicit formulation for the Chebyshev Collocation Spectral Technique using the Runge-Kutta scheme for the time- stepping integration. The partial derivatives in the governing equations were evaluated using Fast Chebyshev Transform (FCT) that allowed to Shrink significantly the processing velocity. The computational code developed was applied to simulated compressible flows under conditions high and low Reynolds numbers (10^3 ≤ Re ≤ 7x10^5 ), either with or without stratiﬁed effect. The results revealed several aspects of the ﬂow structures that in their large part, they accorded with the previous conclusions about the mixing layers. Particularly, it was illustrated the details of density ﬁeld behavior in temporal and spatial mixing layers, enhanced the density rate effect in the turbulent mixing layers. Other important conclusions were taken, using the quantitative results determined by the thermal and kinetic energy cross-correlations.